Emerging pollutants in the environment: A challenge for water resource management - Violette Geissen; Hans Mol; Erwin Klumpp; Günter Umlauf; Marti Nadal; Martine van der Ploeg; Sjoerd E.A.T.M. van de Zee; Coen J. Ritsema (International Soil and Water Conservation Research, 2015)
A significant number of emerging pollutants (EPs) resulting from point and diffuse pollution is present in the aquatic environment. These are chemicals that are not commonly monitored but have the potential to enter the environment and cause adverse ecological and human health effects. According to the NORMAN network, at least 700 substances categorized into 20 classes, have been identified in the European aquatic environment. In light of their potential impact action is urgently required. In this study, we present a concept that shows the current state of art and challenges for monitoring programs, fate and risk assessment tools and requirements for policies with respect to emerging pollutants as a base for sustainable water resource management. Currently, methods for sampling and analysis are not harmonized, being typically focused on certain EP classes. For a number of known highly hazardous EPs detection limits are too high to allow proper risk assessment. For other EPs such as microplastics method development is in its infancy. Advanced ultra-sensitive instrumental techniques should be used for quantitative determination of prioritized EPs in water, suspended matter, soil and biota. Data on EPs' and their metabolites' properties that determine their fate in the environment are often not available. National surveys on water quality often use different parameters for water quality assessment and often do not include EPs. A harmonized monitoring of surface and groundwater is not yet achieved and urgently required. Specific component integrated into models assessing the fate of EPs in a multi compartment environmental approach are missing and must be developed. The main goal of risk assessment is the overall protection of ecological communities in the aquatic environment and human health. New methods for assessing the cumulative risks from combined exposures to several stressors, including mixtures of EPs in a multi-scale approach are required. A combination of regulations and management measures with respect to use/emissions of EPs into the environment, as well as to their occurrence in the environment are fundamental to reach an efficient water resource management.